A 15-Month Survey of Dimethylsulfoniopropionate and Dimethylsulfoxide Content in Posidonia oceanica - Richir, Jonathan; Champenois, Willy; Engels, Guyliann; Abadie, Arnaud; Gobert, Sylvie; Lepoint, Gilles; Silva, João; Santos, Rui; Sirjacobs, Damien; Borges, Alberto V. (Frontiers in Ecology and Evolution, 2020)
Posidonia oceanica is the only reported seagrass to produce significant amount of dimethylsulfoniopropionate (DMSP). It is also the largest known producer of DMSP among coastal and inter-tidal higher plants. Here we studied i) the weekly to seasonal variability and the depth variability of DMSP and its related compound dimethylsulfoxide (DMSO) in P. oceanica leaves of a non-disturbed meadow in Corsica, France, ii) the weekly to seasonal variability and the depth variability of DMSP to DMSO concentration to assess the potential of the DMSP:DMSO ratio as indicator of stress, and iii) the relationships between DMSP, DMSO and the DMSP:DMSO ratio with potential explanatory variables such as light, temperature, photosynthetic activity (effective quantum yield of photosystem II) and leaf size. The overall average concentrations of organosulfured compounds in P. oceanica leaves were 130 ± 39 μmol.gfw-1 for DMSP and 4.9 ± 2.1 μmol.gfw-1 for DMSO. Concentrations of DMSP and DMSO in P. oceanica leaves were overall distinctly higher and exhibited a wider range of variations than other marine primary producers. Concentrations decreased from a maximum in autumn to a minimum in summer; they changed little with depth. Potential explanatory variables except the leaf size, i.e., the leaf age were little or not related to measured concentrations. To explain the seasonal pattern of decreasing concentrations with leaf aging, we hypothesized two putative protection functions of DMSP in young leaves: antioxidant against reactive oxygen species and predator-deterrent. The similar variation of the two molecule concentrations over time and with depth suggested that DMSO content in P. oceanica leaves results from oxidation of DMSP. The DMSP:DMSO ratio remained constant around a mean value of 29.2 ± 9.0 µmol:µmol for the non-disturbed harvested meadow regardless of the time of the year, the depth or the leaf size. As suggested for the salt march plant S. alterniflora, we hypothesized the DMSP:DMSO ratio could be considered as indicator of stress in seagrasses exposed to environmental or anthropogenic stressors. More research would now be needed to confirm the functions of DMSP and DMSO in seagrasses and how the DMSP:DMSO ratio will vary under various disturbances.